2020
DOI: 10.1002/ldr.3614
|View full text |Cite
|
Sign up to set email alerts
|

Land management to reconcile ecosystem services supply and demand mismatches—A case study in Shanghai municipality, China

Abstract: City managers need to understand how land use and land cover (LULC) change in an urban landscape can affect future land degradation and conditions for ecosystem services (ESs) supply and demand. Optimal land use and land management requires explicit spatial mapping of ESs supply and demand under alternative land use scenarios. In this study, we applied spatially explicit models to predict changes in ESs supply and demand, and their coupling mechanisms, under one baseline scenario and three stakeholder-defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Based on the photosynthesis and respiration data of the vegetation, 1.63 units of carbon can be sequestered, and 1.2 units of oxygen can be released for every unit of NPP accumulated by the vegetation [ 32 ]. The value of carbon sequestration and oxygen release services were calculated using Formulae (2) and (3).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the photosynthesis and respiration data of the vegetation, 1.63 units of carbon can be sequestered, and 1.2 units of oxygen can be released for every unit of NPP accumulated by the vegetation [ 32 ]. The value of carbon sequestration and oxygen release services were calculated using Formulae (2) and (3).…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, we could explain why only considering the potential supply of ES and restoration costs would result in priority areas being concentrated in Chongming District (Figure 4A). Specifically, recent studies have shown that ES supply was lower than human demand in Baoshan District and the central Pudong New Area due to anthropogenic impacts (e.g., huge demand for land resources on industrial, residential, and commercial development; Chen et al, 2019;Jiang et al, 2020;Shi et al, 2020). The restoration costs in the two districts were much higher than those in Chongming District, which can be attributed to the high opportunity costs represented by local high housing prices (SMSB and SONBS, 2017).…”
Section: Significance Of Incorporating Es Demand-supply Ratio Index I...mentioning
confidence: 99%
“…The continuous improvement of human well-being is the main objective for social development and the vision of human society [ 1 , 2 ]. Former research on human well-being mainly focused on economics, sociology, and social sciences, while the contribution of the ecological environment to human well-being has not received enough attention [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…As human demand for ESs affects the functioning of the whole ecosystem, the need for systematic management of ecosystem services can no longer be met by considering only the ESs supply [ 14 ]. Therefore, more scholars have become interested in the relationship between ESs supply and ESs demand [ 15 ], and they have conducted numerous theoretical [ 16 ], methodological [ 17 ], and practical studies [ 1 ]. Current research focuses on the supply and demand for services of a single ecosystem type, ranging from provision services [ 18 ] to regulating services [ 19 ] and cultural services [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation